2021
DOI: 10.1021/acsphotonics.1c01356
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Dielectric Nanoantennas and Metasurfaces: Frequency Conversion and Wavefront Control

Abstract: High-index dielectric nanostructures can support optical resonances of electric and magnetic character with ultralow linear absorption. In contrast to plasmonics, they can be engineered to confine electromagnetic fields inside the resonator, amplifying intrinsic nonlinearities of the dielectric. In this Review I examine the ability of dielectric nanoantennas and metasurfaces for efficient harmonic generation and wave-mixing processes, as well as nonlinear wavefront manipulation of the incident and radiated lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 216 publications
(427 reference statements)
0
39
0
Order By: Relevance
“…Excellent reviews can be found in ref. 145,147,148 . They are structured by definition and can combine wavelength conversion with wavefront control 149−151 , spin-orbit interactions 152 , OAM operations involving SAM 143 , image encoding 153 and optical activity 154 .…”
Section: Metasurfacesmentioning
confidence: 99%
“…Excellent reviews can be found in ref. 145,147,148 . They are structured by definition and can combine wavelength conversion with wavefront control 149−151 , spin-orbit interactions 152 , OAM operations involving SAM 143 , image encoding 153 and optical activity 154 .…”
Section: Metasurfacesmentioning
confidence: 99%
“…Consequently, all-dielectric nanoparticles with high refractive indices, large nonlinear coefficients, and low losses have been used in building enhanced optical nonlinear processes over the past few years. Such nanoparticles support Mie resonances which enable the enhanced harmonic generations, including second-harmonic generation (SHG), third-harmonic generation (THG), and four-wave mixing (FWM) [14][15][16][17][18][19][20][21][22]. Mie-type resonances can provide strong local field confinement inside the nanostructure and thus enhance the nonlinear conversion efficiency from the resonant nanostructures [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…However, introducing all‐dielectric nanostructures made of high refractive index materials with strong nonlinear coefficients allows us to boost the nonlinear conversion efficiency by several orders and introduce certain functionalities. [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ] These high index nanostructures support diverse spatial electromagnetic modes to couple the nonlinear coefficients of the material to the external electromagnetic field. Two important categories of these modes in the context of nonlinear optics are the Mie modes and the bound states in the continuum (BIC).…”
Section: Introductionmentioning
confidence: 99%